Alkylated alkali lignin for compatibilizing agents of carbon fiber-reinforced plastics with polypropylene. Issue 3 (March 2018) - Sakai, Hiroki; Kuroda, Kosuke; Muroyama, Shiori; Tsukegi, Takayuki; Kakuchi, Ryohei; Takada, Kenji; Hata, Ayano; Kojima, Ryosuke; Ogoshi, Tomoki; Omichi, Masaaki; Ninomiya, Kazuaki; Takahashi, Kenji
Abstract As an alternative to petroleum-based compatibilizing agents, we developed lignin derivatives for compatibilizing agents of carbon fiber-reinforced plastics that have thermoplasticity. In this study, alkyl chains were introduced into alkali lignin at various ratios to optimize the compatibility of the lignin derivatives with both polypropylene and carbon fiber. The interfacial shear strength between the two materials was improved from 8.2 to 17.2 MPa by mixing with the optimized lignin derivative. The value is comparable to that achieved with a typical petroleum-based compatibilizing agent (18.3 MPa). Lignin-derived compatibilizing agents were developed for polypropylene-based carbon fiber-reinforced prastics. Introduction of acyl groups to alkali lignin improved compatibility of the lignin to both carbon fiber and polypropylene while underivatized alkali lignin did not show compatibility. The interfacial shear strength between carbon fiber and polypropylene was significantly improved by addition of the lignin derivatives as compatibilizing agents.